Understanding the mechanism of Pd-catalyzed allylic substitution of the cyclic difluorinated carbonates - Xu, Jun; Qiu, Xiao-Long; Qing, Feng-Ling (Beilstein Journal of Organic Chemistry, 2008)
We present a mechanistic investigation of Pd-catalyzed allylic substitution of cyclic gem-difluorinated carbonates 1 and 4, previously employed in the synthesis of 3',3'-difluoro-2'-hydroxymethyl-4',5'-unsaturated carbocyclic nucleosides in 17 steps. The substitution features a reversal of regioselectivity caused by fluorine.

(untitled) - Marquez, V. E. (Adv. Antiviral Drug Des., 1996)

(untitled) - Zhu, X.-F. (Nucleosides, Nucleotides Nucleic Acids, 2000)

(untitled) - Santana, L.; Teijeira, M.; Uriarte, E.; Terán, C.; Casellato, U.; Graziani, R. (Nucleosides Nucleotides, 1996)

(untitled) - Escuredo, V.; Ferro, B.; Santana, L.; Teijeira, M.; Uriarte, E. (Nucleosides Nucleotides, 1997)

(untitled) - Besada, P.; Terán, C.; Teijeira, M.; Uriarte, E. (Nucleosides Nucleotides, 1999)

(untitled) - Terán, C.; González-Moa, M. J.; Mosquera, R.; Santana, L. (Nucleosides, Nucleotides Nucleic Acids, 2001)

(untitled) - Santana, L.; Teijeira, M.; Terán, C.; Uriarte, E.; Viña, D. (Synthesis, 2001)

(untitled) - Besada, P.; González-Moa, M. J.; Terán, C.; Santana, L.; Uriarte, E. (Synthesis, 2002)

(untitled) - González-Moa, M. J.; Besada, P.; Teijeira, M.; Terán, C.; Uriarte, E. (Synthesis, 2004)

(untitled) - Estrada, E.; Uriarte, E.; Montero, A.; Teijeira, M.; Santana, L.; De Clercq, E. (J. Med. Chem., 2000)

(untitled) - Yang, Y.-Y.; Xu, J.; You, Z.-W.; Xu, X.-H.; Qiu, X.-L.; Qing, F.-L. (Org. Lett., 2007)

(untitled) - Konno, T.; Ishihara, T.; Yamanaka, H. (Tetrahedron Lett., 2000)

(untitled) - Konno, T.; Daitoh, T.; Ishihara, T.; Yamanaka, H. (Tetrahedron: Asymmetry, 2001)

(untitled) - Okano, T.; Matsubara, H.; Kusukawa, T.; Fujita, M. (J. Organomet. Chem., 2003)

(untitled) - Konno, T.; Takehana, T.; Ishihara, T.; Yamanaka, H. (Org. Biomol. Chem., 2004)

(untitled) - Konno, T.; Nagata, K.; Ishihara, T.; Yamanaka, H. (J. Org. Chem., 2002)

(untitled) - Konno, T.; Takehana, T.; Mishima, M.; Ishihara, T. (J. Org. Chem., 2006)

(untitled) - Nokami, J.; Matsuura, H.; Nakasima, K.; Shibata, S. (Chem. Lett., 1994)

(untitled) - Szabó, K. J. (Chem. Soc. Rev., 2001)

(untitled) - Macsári, I.; Hupe, E.; Szabó, K. J. (J. Org. Chem., 1999)

(untitled) - Hoke, M. E.; Brescia, M.-R.; Bogaczyk, S.; DeShong, P.; King, B. W.; Crimmins, M. T. (J. Org. Chem., 2002)

(untitled) - Jonasson, C.; Kritikos, M.; Bäckvall, J.-E.; Szabó, K. J. (Chem.–Eur. J., 2000)

(untitled) - Kurosawa, H.; Ogoshi, S.; Kawasaki, Y.; Murai, S.; Miyoshi, M.; Ikeda, I. J. (J. Am. Chem. Soc., 1990)